FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN APARATUR PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA MAKASSAR - Andi Irwan Kasim (Program Studi Perbankan Syariah, IAIN Palopo, 2023)
This research aims to analyze the influence of communication competence and professionalism partially and simultaneously on the quality of service for officials at the Makassar City Population and Civil Registry Service. The research method used is quantitative descriptive research. The research sample consisted of 79 respondents. Sampling uses saturated/census sampling, meaning the entire population is used as a sample. The data analysis methods used are data quality test, classical assumption test, multiple linear regression, t test, F test and coefficient of determination. The results of the research show that communication competence partially has a positive and significant effect on the quality of apparatus services, professionalism partially has a positive and significant effect on the quality of apparatus services, communication competence and professionalism simultaneously have a positive and significant effect on the quality of apparatus services.